Induction of microRNA-199 by Nitric Oxide in Endothelial Cells Is Required for Nitrovasodilator Resistance via Targeting of Prostaglandin I2 Synthase. Issue 4 (24th July 2018) - Bai, Yong-Ping; Zhang, Jia-Xiong; Sun, Quan; Zhou, Ji-Peng; Luo, Jing-Min; He, Ling-Fang; Lin, Xing-Chi; Zhu, Ling-Ping; Wu, Wan-Zhou; Wang, Zhen-Yu; Zhang, Guo-Gang
Abstract : Background: Nitrates are widely used to treat coronary artery disease, but their therapeutic value is compromised by nitrate tolerance, because of the dysfunction of prostaglandin I2 synthase (PTGIS). MicroRNAs repress target gene expression and are recognized as important epigenetic regulators of endothelial function. The aim of this study was to determine whether nitrates induce nitrovasodilator resistance via microRNA-dependent repression of PTGIS gene expression. Methods: Nitrovasodilator resistance was induced by nitroglycerin (100 mg·kg –1 ·d –1, 3 days) infusion in Apoe –/– mice. The responses of aortic arteries to nitric oxide donors were assessed in an organ chamber. The expression levels of microRNA-199 (miR-199)a/b were assayed by quantitative reverse transcription polymerase chain reaction or fluorescent in situ hybridization. Results: In cultured human umbilical vein endothelial cells, nitric oxide donors induced miR-199a/b endogenous expression and downregulated PTGIS gene expression, both of which were reversed by 2-(4-carboxyphenyl)-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt or silence of serum response factor. Evidence from computational and luciferase reporter gene analyses indicates that the seed sequence of 976 to 982 in the 3′-untranslated region of PTGIS mRNA is a target of miR-199a/b. Gain functions of miR-199a/b resulting from chemical mimics or adenovirus-mediated overexpression increased PTGIS mRNA degradation in HEK293 cells and human umbilical vein endothelial cells. Furthermore, nitroglycerin-decreased PTGIS gene expression was prevented by miR-199a/b antagomirs or was mirrored by the enforced expression of miR-199a/b in human umbilical vein endothelial cells. In Apoe –/– mice, nitroglycerin induced the ectopic expression of miR-199a/b in the carotid arterial endothelium, decreased PTGIS gene expression, and instigated nitrovasodilator resistance, all of which were abrogated by miR-199a/b antagomirs or LNA—anti–miR-199. It is important that the effects of miR-199a/b inhibitions were abolished by adenovirus-mediated PTGIS deficiency. Moreover, the enforced expression of miR-199a/b in vivo repressed PTGIS gene expression and impaired the responses of aortic arteries to nitroglycerin/sodium nitroprusside/acetylcholine/cinaciguat/riociguat, whereas the exogenous expression of the PTGIS gene prevented nitrovasodilator resistance in Apoe –/– mice subjected to nitroglycerin infusion or miR-199a/b overexpression. Finally, indomethacin, iloprost, and SQ29548 improved vasorelaxation in nitroglycerin-infused Apoe –/– mice, whereas U51605 induced nitrovasodilator resistance. In humans, the increased expressions of miR-199a/b were closely associated with nitrate tolerance. Conclusions: Nitric oxide–induced ectopic expression of miR-199a/b in endothelial cells is required for nitrovasodilator resistance via the repression of PTGIS gene expression. Clinically, miR-199a/b is a novel target for the treatment of nitrate tolerance. Abstract : Supplemental Digital Content is available in the text.